2008
DOI: 10.1111/j.1744-6198.2008.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Going the Extra Mile: Beyond Health Teaching to Political Involvement

Abstract: These RN-BSN students successfully demonstrated their ability to move beyond a focus on individuals to embrace the concept of community as client. In the process, they honed their skills in advocacy, communication, and political involvement, and achieved all of their BSN program's objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Students Seventeen articles featured medicine students, [1,14,16,21,[24][25][26][29][30][43][44][45][46][47][48][49][50] 20 featured nursing students, [15,[17][18][19][20][27][28][31][32][33][34][35][36][37][38][39][40][41][42][51][52][53][54] and four featured pharmacy students. [34,39,41,55] The earliest article was published in 1999 (medicine), followed by a 2000 article (nursing).…”
Section: Resultsmentioning
confidence: 99%
“…Students Seventeen articles featured medicine students, [1,14,16,21,[24][25][26][29][30][43][44][45][46][47][48][49][50] 20 featured nursing students, [15,[17][18][19][20][27][28][31][32][33][34][35][36][37][38][39][40][41][42][51][52][53][54] and four featured pharmacy students. [34,39,41,55] The earliest article was published in 1999 (medicine), followed by a 2000 article (nursing).…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Students have acknowledged the power of a political voice in population health, their own professional development, and the ability to sharpen advocacy skills as key components in developing political awareness. [21][22][23][24] Advocacy is not without barriers. Lack of interest and apathy regarding macro-level politics have been explored as they affect the nursing profession.…”
Section: Methodsmentioning
confidence: 99%
“…Students have experienced increased political awareness and empowerment and have developed critical thinking skills needed for political competence. [21][22][23][24] Relationships formed with coalitions, interest groups, and state and evaluate a legislative advocacy project. Table 1 outlines the basic components of the assessment, planning, implementation, and evaluation phases of the project over a seven-week time frame.…”
mentioning
confidence: 99%
“…Methods of teaching advocacy skills vary between universities and disciplines. One nursing program found that the best way to teach their students about advocacy was through community immersion (Wold, Brown, Chastain, Griffis, & Wingate, 2008). Once the students felt more familiar with the community and its health issues, they felt empowered to learn about and engage with the policy landscape (Wold et al, 2008).…”
Section: Student Advocacymentioning
confidence: 99%
“…One nursing program found that the best way to teach their students about advocacy was through community immersion (Wold, Brown, Chastain, Griffis, & Wingate, 2008). Once the students felt more familiar with the community and its health issues, they felt empowered to learn about and engage with the policy landscape (Wold et al, 2008). Course assignments that provide undergraduate students the opportunity to practice advocacy have proven effective at increasing students’ positive beliefs about advocacy (Goodhart, 2002; Massengale, Childers-McKee, & Benavides, 2014).…”
Section: Student Advocacymentioning
confidence: 99%